The Spread of Christianity and Islam in the Early Modern Period in Relation to Strategies for Localizing These Faiths - Ziying Sui (Studies in Social Science & Humanities, 2023)
Since the sixteenth century, Christianity and Islam have evolved into global religions through the efforts of missionaries, spreading throughout the world and gaining widespread acceptance among local populations. The wide spread of religion cannot be separated from the strategies for localizing these faiths. This article discusses in detail the application and impact of localization strategies in the early modern period spread of Christianity and Islam to enrich scholarly research on religious communication strategies.